2023
DOI: 10.3201/eid2905.230028
|View full text |Cite
|
Sign up to set email alerts
|

Case Report and Literature Review of Occupational Transmission of Monkeypox Virus to Healthcare Workers, South Korea

Abstract: We report a case of occupational monkeypox virus infection from a needlestick injury in a healthcare worker in South Korea and review similar reports in the literature during 2022. Postexposure prophylactic treatment with a third-generation smallpox vaccine and antiviral agent tecovirimat inhibited local virus spread and alleviated lesion pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 11 publications
0
12
0
2
Order By: Relevance
“…9 Nevertheless, occupational MPXV-transmission in health care settings is a rare event primarily associated with needlestick injuries or violation of hygiene rules, both of which did not occur in our setting. [10][11][12][13] In the literature, only three nosocomial transmission events through fomite exposure have been reported during the large 2022 Mpox outbreak. [10][11][12][13] Given the rarity of nosocomial transmission as reported in the literature, [10][11][12][13] and the absence of transmission despite extensive exposure of a large number of HCW in our setting, it seems justified to dispense quarantine of HCW in case of non-percutaneous exposure and instead perform close active surveillance.…”
Section: Lack Of Monkeypox Virus (Mpxv) Transmission Despite Occupati...mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Nevertheless, occupational MPXV-transmission in health care settings is a rare event primarily associated with needlestick injuries or violation of hygiene rules, both of which did not occur in our setting. [10][11][12][13] In the literature, only three nosocomial transmission events through fomite exposure have been reported during the large 2022 Mpox outbreak. [10][11][12][13] Given the rarity of nosocomial transmission as reported in the literature, [10][11][12][13] and the absence of transmission despite extensive exposure of a large number of HCW in our setting, it seems justified to dispense quarantine of HCW in case of non-percutaneous exposure and instead perform close active surveillance.…”
Section: Lack Of Monkeypox Virus (Mpxv) Transmission Despite Occupati...mentioning
confidence: 99%
“…[10][11][12][13] In the literature, only three nosocomial transmission events through fomite exposure have been reported during the large 2022 Mpox outbreak. [10][11][12][13] Given the rarity of nosocomial transmission as reported in the literature, [10][11][12][13] and the absence of transmission despite extensive exposure of a large number of HCW in our setting, it seems justified to dispense quarantine of HCW in case of non-percutaneous exposure and instead perform close active surveillance. Nevertheless, Mpox should be considered early in high-risk patients with vesicular lesions to implement infection control measures and postexposure vaccination without delay to prevent further MPXV transmission.…”
Section: Lack Of Monkeypox Virus (Mpxv) Transmission Despite Occupati...mentioning
confidence: 99%
“…Since immunocompromised people are more likely to become really ill with mpox and even die from the virus, the spread of mpox among more susceptible populations could have more devastating health consequences. Nurses and other healthcare workers have a crucial role in preventing the spread of mpox from person to person by educating the public and responding quickly to confirmed cases with isolation, contact tracing, clinical management, and infection prevention measures ( Aden et al, 2023 ; Ahmed, Abdulqadir, Omar, Hussein, Qurbani, Mohamed, et al, 2023 ; Choi et al, 2023 ).…”
Section: Brief Reviewmentioning
confidence: 99%
“…People at highest risk tended to be those living in endemic rural communities, 44,48 those in close contact with infected animals, 27,48 people who hunted, ate, or handled infected wild animals, 42,46 those who travelled to endemic regions, 50,51 people who had not received the smallpox vaccine (which provides cross-protection), 57,58 and healthcare workers involved in diagnosing, treating, and caring for Mpox patients. 59,60 By contrast, in the 2022 Mpox outbreak, individuals in the European and American continents were primarily affected. They had little or no connection with endemic regions or contact with infected animals.…”
Section: Who Was At Risk Of Getting Monkeypox?mentioning
confidence: 99%
“…Although everyone is potentially susceptible to infection with the Mpox virus, survey of confirmed or suspected cases over the last 50 years, indicated that certain groups were primary affected. People at highest risk tended to be those living in endemic rural communities, 44,48 those in close contact with infected animals, 27,48 people who hunted, ate, or handled infected wild animals, 42,46 those who travelled to endemic regions, 50,51 people who had not received the smallpox vaccine (which provides cross‐protection), 57,58 and healthcare workers involved in diagnosing, treating, and caring for Mpox patients 59,60 . By contrast, in the 2022 Mpox outbreak, individuals in the European and American continents were primarily affected.…”
Section: Who Was At Risk Of Getting Monkeypox?mentioning
confidence: 99%